Roles for HB‐EGF in Mesenchymal Stromal Cell Proliferation and Differentiation During Skeletal Growth. (14th December 2018) - Li, Ping; Deng, Qi; Liu, Jiajia; Yan, Jianshe; Wei, Zhanying; Zhang, Zhenlin; Liu, Huijuan; Li, Baojie
ABSTRACT: HB‐EGF, a member of the EGF superfamily, plays important roles in development and tissue regeneration. However, its functions in skeletal stem cells and skeleton development and growth remain poorly understood. Here, we used the Cre/LoxP system to ablate or express HB‐EGF in Dermo1+ mesenchymal stromal cells and their progenies, including chondrocytes and osteoblast lineage cells, and bone marrow stromal cells (BMSCs). Dermo1‐Cre; HB‐EGF f/f mice only showed a modest increase in bone mass, whereas Dermo1‐HB‐EGF mice developed progressive chondrodysplasia, chondroma, osteoarthritis‐like joint defects, and loss of bone mass and density, which were alleviated by treatment with EGFR inhibitor AG1478. The cartilage defects were recapitulated in chondrocyte‐specific HB‐EGF overexpression ( Col2‐HB‐EGF ) mice with a lesser severity. Dermo1‐HB‐EGF mice showed an increase in proliferation but defects in differentiation of chondrocytes and osteoblasts. HB‐EGF promoted BMSC proliferation via the Akt1 and Erk pathways but inhibited BMSC differentiation via restraining Smad1/5/8 activation. However, Dermo1‐HB‐EGF mice showed normal osteoclastogenesis and bone resorption. These results reveal an important function of autocrine or paracrine HB‐EGF in mesenchymal stromal cell proliferation and differentiation and suggest that EGF signaling needs to be tightly controlled to maintain bone and articular cartilage integrity. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.